"BETWEEN STORIES AND EXPERIENCES: WORKSHOP ON LITERACY AND INTERSECTIONALITY" (CIPEEX, 2025)
This report describes the experience of developing a group script and activity for the implementation of a workshop with workers from NASSA (Núcleo de Apoio à Saúde do Servidor de Anápolis), aimed at promoting reflections on literacy and intersectionality in the context of workers’ health. The workshop sought to create a space for dialogue and knowledge exchange, addressing how gender, race, and social class issues intersect in these women’s lives and directly impact their health, rights, and daily work experiences.This work was carried out by Group 4 of the PET-Saúde Equidade Program and aimed to develop and apply a script for a workshop on literacy and intersectionality. Initially, a conceptual review of the topics was conducted, followed by the collective construction of the script, including dynamics, audiovisual resources, and moments of dialogue with the audience.After completion, the script was applied as a rehearsal with the PET-Saúde student group itself, allowing practical experimentation and refinement of the proposals. This phase had a methodological and formative character, enabling the assessment of the clarity of the facilitation, the relevance of the activities, and the appropriateness of the language used. The dynamic will later be applied to the target population.During the script construction, the group recognized the importance of integrating theoretical concepts in an accessible way connected to participants’ realities, using resources such as videos, film excerpts, and guided discussions, structuring the entire dynamic through a discussion circle so that participants could freely express themselves at any time. The selection of the short film Corpo Preto and the development of interactive activities were evaluated as effective strategies to provoke critical reflection on literacy and intersectionality.In the workshop rehearsal with the PET-Saúde group, important aspects were revealed: the need for better time management, the importance of building a collective word map to create content together with participants, the relevance of guiding questions to stimulate active participation, and the power of teamwork in facilitating the workshop. Additionally, the exercise demonstrated how the simulation process itself promoted students’ literacy and expanded collective understanding of equity and intersectionality.In conclusion, the creation of the group workshop project was a transformative experience, capable of sensitizing and mobilizing workers to reflect on the social determinants of health that affect them, reinforcing the importance of health education as a tool for empowerment and comprehensive care.